Space-Time Recovery of Arbitrarily Shaped Wave-Packets by Means of Three Dimensional Imaging Technique - Matijošius, A.; Piskarskas, R.; Gaižauskas, E.; Dubietis, A.; Di Trapani, P. (Nonlinear Analysis: Modelling and Control, 2004)
We study numerically and experimentally self-focusing dynamics of femtosecond light pulses. By demonstrating the potential of three dimensional imaging technique for quantitative recovery of complex (arbitrarily shaped) wave packets, we monitor space-time transformation dynamics of 150-fs light pulse, which undergoes self-focusing and filamentation in water. Peculiar spatiotemporal and spectral features reveal conical nature of resulting wave-packet.